Kualitas Pelayanan Surat Ijin Mengemudi (SIM) pada Masa Pandemi Covid-19 di Polrestabes Semarang - Didi Dewantoro; Kismartini Kismartini; Ida Hayu Dwimawanti (Universitas Medan Area, 2022)
During the Covid 19 pandemic, driver’s license or SIM services at the Semarang Polrestabes Satpas Unit Office were limited, with the aim of avoiding crowds and interactions in order to prevent the spread of the Covid 19 virus. Service time for SIM test participants was limited, service officers were limited, as was the number of people taking SIM test participants. restrictions are made. This affects the quality of service to the people who take the SIM test participants. This study aims to investigate the quality of service for a driver's license (SIM) during the Covid-19 pandemic at the Semarang Police Station. The results showed that the quality of service provided by Polrestabes Semarang did not meet the expectations of the community because the calculated quality value (Q) had a result of less than (≤) 1. The obstacle faced was the need for priority on completeness in the context of health protocols that were still lacking both officers and the public. service users, lack of cleanliness of infrastructure and service officers who are still lacking. The solution when viewed from Quadrant A of the Cartesian diagram of the Servqual model, the attributes of community needs that are the main priority and must be improved are the condition of clean bathrooms, neat appearance of officers by implementing health protocols, officers paying more attention to users, especially during the pandemic to maintain distance and keep 50% capacity; the price of the appropriate SIM product, the ease of payment, the guarantee comes first if there is an error on the officer, the solution is given in experiencing public complaints about SIM services. And the solution that can be given is to complete the Covid-19 pandemic attribute equipment including symbols marking social distancing, providing handwashing and soap in several corners of the service room, as well as being disciplined in using masks by officers and also providing masks for people who come without wearing masks, completing the list of available services, increasing the knowledge of officers regarding SIM services provided to answer all forms of community questions, and making it easier for all people to get services without discrimination.